Perioperative management of thyroglossal duct cystectomy in a pediatric patient: A case report. Issue 2 (4th December 2020) - Sato (Boku), Aiji; Kako, Eisuke; Okuni, Nozomi; Kusama, Nobuyoshi; Kamimura, Yuji; Sento, Yoshiki; So, MinHye; Tanaka, Motoshi; Miyamoto, Hironori; Kato, Shinichiro; Kobayashi, Masaki; Shibuya, Yasuyuki; et al.
Abstract: Thyroglossal duct on the dorsum of the tongue in the pediatric patient can cause a difficult airway due to the large mass and risk of airway obstruction associated with a swollen tongue after surgery. Abstract : Careful airway management in the perioperative period contributed to the prevention of the occurrence of respiratory complications.